Are remitted affective disorders and familial risk of affective disorders associated with metabolic syndrome, inflammation and oxidative stress? – a monozygotic twin study. Issue 10 (4th July 2020) - Ottesen, Ninja Meinhard; Meluken, Iselin; Frikke-Schmidt, Ruth; Plomgaard, Peter; Scheike, Thomas; Fernandes, Brisa S.; Berk, Michael; Poulsen, Henrik Enghusen; Kessing, Lars Vedel; Miskowiak, Kamilla; Vinberg, Maj
Abstract: Background: Metabolic syndrome (MetS) is associated with reduced life expectancy in patients with affective disorders, however, whether MetS also plays a role before the onset of affective disorder is unknown. We aimed to investigate whether MetS, inflammatory markers or oxidative stress act as risk factors for affective disorders, and whether MetS is associated with increased inflammation and oxidative stress. Methods: We conducted a high-risk study including 204 monozygotic (MZ) twins with unipolar or bipolar disorder in remission or partial remission (affected), their unaffected co-twins (high-risk) and twins with no personal or family history of affective disorder (low-risk). Metabolic Syndrome was ascertained according to the International Diabetes Federation (IDF) criteria. Inflammatory markers and markers of oxidative stress were analyzed from fasting blood and urine samples, respectively. Results: The affected and the high-risk group had a significantly higher prevalence of MetS compared to the low-risk group (20% v. 15% v. 2.5%, p = 0.0006), even after adjusting for sex, age, smoking and alcohol consumption. No differences in inflammatory and oxidative markers were seen between the three groups. Further, MetS was associated with alterations in inflammatory markers, and oxidative stress was modestly correlated with inflammation. Conclusion: Metabolic syndrome is associated with low-grade inflammation and may act as a risk factor and a trait marker for affective disorders. If confirmed in longitudinal studies, this suggests the importance of early intervention and preventive approaches targeted towards unhealthy lifestyle factors that may contribute to later psychopathology.